Peran Karang Taruna Sopa Bersatu Dalam Mengelola Inovasi Cuka Aren Di Desa Sopa - Jusriani; Arif, Andi Tri Wahyuni; Azhizhah , Nurul; Bahrun , St. Rahmaniah (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Karang Taruna is a youth organization in Indonesia formed by the community as a forum for the younger generation to develop themselves, grow, and develop on the basis of awareness and social responsibility from, by, and the younger generation that is oriented towards achieving social welfare for the community. In addition to the village head, youth organizations also have an important role in developing the village. As a youth organization, youth organizations must be creative, innovative and make new breakthroughs, especially in developing villages and overcoming problems in the village such as economic, social, environmental problems, etc. Therefore, youth organizations have strategic roles and tasks and are closely related to the village government. This study aims to describe the role of the Sopa Youth Organization in the management of palm vinegar in Sopa Village, Bulukumba Regency. This research is a type of qualitative research with a descriptive approach with purposive sampling technique and data collection methods with observation, interview and documentation techniques. The results showed that the role of the united Sopa Youth Organization in managing palm vinegar was as (1) the initiator of the idea. This is motivated by complaints from palm farmers who complain about the difficulty of marketing palm sugar and to reduce the manufacture or consumption of ballo kacci (Bugis liquor). (2) manufacturers. Apart from being the initiator of ideas, youth organizations also play a role in producing palm vinegar innovations. (3) distributors. The united Sopa Youth Organization also plays a role in distributing goods produced from producers to consumers.